Real Wage Convergence in Romania: Empirical Evidence Based on Club Converging - Neagu, Olimpia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The study aims to explore the real wage convergence across the 42 Romanian counties from 1991 to 2016 by using the convergence algorithm developed by Phillips and Sul (2007). The process of divergence is identified in the period of 1991-2016 as well as a number of 4 convergence subgroups (clusters). Transitional curves indicate that over the long-run the real wage tends to converge. Policy implications of the paper's findings are also provided.